Site and depth influence on coral reef structure and composition in Seribu Islands, Jakarta - Karizma Fahlevy; Siti Khodijah; Idham A. Nasrullah; Ridha Fathihatunnisa; Beginer Subhan; Hawis Madduppa (Aceh Journal of Animal Science, 2017)
The coral reefs structure and composition are influenced by environmental condition and depth. Therefore, this study was conducted to find and examine the influence of depth against coral reef structures in Pramuka Island regions, Seribu Islands, located in the northern of Jakarta. The study was carried out from November to December 2016.The data was taken by using Line Intercept Transect Method which is laid 20 meters x 3 replication parallels with shoreline at the depth of 3 and 10 meters. There was a dominant of higher hard coral (HC) coverage recorded at the depth of 3 m and the lowest percentage located in West of Pramuka. Coral mortality index varied and ranged from 0.39 to 0.98. West of Pramuka Island dominant have the lowest value of average number of families, genera, and life form. Percentage of hard coral cover, coral mortality index, average number of family, genera, and life form differed significantly between sites. The different of depth only influencing the percentage of coral cover and average number of life form.